“Red Housekeeping” in a Socialist Factory: Jiashu and Transforming Reproductive Labor in Urban China (1949–1962) - Dong, Yige (International review of social history, 2024)
While scholarship on “women's liberation” under historically existing socialism focuses on heroic women making inroads into male-dominated domains, this article explores a previously overlooked group of women in socialist China. Known as jiashu in Chinese, these women are the female dependents (wives, mothers, and in-laws) of both male and female employees in a workplace. Specifically, it centers on the experiences of the jiashu of textile workers in the city of Zhengzhou from 1949 to 1962. It argues that, despite being portrayed as “parasitizing” off formal workers, jiashu performed a wide range of work, both paid and unpaid, inside and outside the household. Similar to their counterparts under capitalism and other state-socialist regimes, these Chinese women's unpaid domestic work sustained the daily and generational reproduction of the labor force and was thus essential to industrial accumulation. Moreover, jiashu also worked on the shopfloor and in collectivized service facilities as paid laborers. Such remunerated work also subsidized accumulation, and the resistance from these women contributed to the eventual collapse of the Great Leap Forward (1958–1962). This research advances the field in two ways. First, it expands theories about the relationship between women's work, social reproduction, and capital accumulation to include work that is both reproductive in nature and remunerated – a previously understudied form of labor. Second, while existing literature focuses on structural analysis and explains why women's work is functional to accumulation, this study gives equal attention to women's agency, showing how interactions between the two shaped historical trajectories.